CAPE and convective events in the southwest during the North American monsoon - Adams, David K.; Souza, Enio P. (Monthly Weather Review, 2009)
The relationship between atmospheric stability, measured as CAPE, and deep precipitating convection has been widely studied but is not definitive. In the maritime tropics, CAPE and precipitation are usually inversely correlated. In continental convection (i.e., midlatitude and tropical), no consistent relationship has been found. In this study of the semiarid Southwest, a moderate positive correlation exists, approaching 0.6. Correlations based on radiosonde data are found to be sensitive to the parcel level of origin. The strongest correlations are found by modifying the preconvective morning sounding with the maximum reported surface temperature, assuming well-mixed adiabatic layers to the level of free convection with pseudoadiabatic ascent. These results show that the upper bounds on parcel instability correlate best with precipitation. Furthermore, the CAPE-precipitation relationship is argued to depend on the convective regime being considered. The North American monsoon convective regime requires essentially only moisture advection interacting with the strong surface sensible heating over complex topography. Elimination of strong convective inhibition through intense surface sensible heating in the presence of sufficient water vapor leads to the positive CAPE-precipitation relationship on diurnal time scales. These results are discussed in light of contradictory results from other continental and maritime regions, which demonstrate negative correlations. © 2009 American Meteorological Society.
Keywords: Atmospheric Stabilities; Complex Topographies; Convective Events; Convective Inhibitions; Free Convections; Midlatitude; Moisture Advections; Negative Correlations; North Americans; Positive Correlations; Radiosonde Datum; Surface Temperatures; Time-scale; Upper Bounds; Heating; Water Vapor; Surface Topography; Atmospheric Convection; Convective System; Correlation; Monsoon; Precipitation (climatology); North America